THE EXISTENCE OF BITCOIN IN THE PERSPECTIVE OF MAQASID AL-SYAR‘IYAH - Dara Lidia; Jabbar Sabil; Syarifuddin Usman (LKKI Fakultas Syariah dan Hukum Universitas Islam Negeri Ar-Raniry, 2018)
Historically, the means of payment has evolved from time to time. The current phenomenon is Bitcoin, claimed by its users as a means of future payments, that have been the major attention of many people, from people in business to students. The research question in this study was how the existence of Bitcoin as a medium of exchange is, and how its existence as a medium of exchange is viewed based on the maqāṣid al-syar 'īyah. This used the literature research method and the maqāṣidī approach by applying the tarjih maslahat method. The existence of Bitcoin as a medium of exchange is considered valid because of the 'urf recognition. However, it requires a legal status from the government because it is related to al-maslahat al-mmāmmah, the mafsadat (damage) value of Bitcoin is higher than its maslahat (benefit) value. Hence, it is concluded that Bitcoin is valid as a medium of exchange. Still, its use must be limited due to the mafsadat (harm) probability that is more dominant at the ḍarūriyyāt (primary needs) level, following the principle of